Genetic and Environmental Influences on Individual Differences in Sleep Duration During Adolescence. (4th November 2013) - te Velde, Saskia J.; van der Aa, Niels; Boomsma, Dorret I.; van Someren, Eus J. W.; de Geus, Eco J. C.; Brug, Johannes; Bartels, Meike
Abstract : This study assessed to what extent genetic and environmental factors contributed to individual differences in adolescent sleep duration, and whether genetic and environmental contributions to sleep duration changed throughout adolescence. A twin-family design was used to gain insight into the genetic and environmental contributions to variation in sleep duration. The study sample consisted of 6, 319 adolescent twins (44% males) and 1, 359 non-twin siblings (44% males) in the age range of 12 to 20 years (mean age = 16.85, SD = 1.40). The participants self-reported usual sleep duration, which was categorized as less than 8 hours per night, 8–9 hours per night, and more than 9 hours per night. Results showed that the prevalence of shorter than optimum sleep duration, that is, less than 8 hours per night, was high, with the highest prevalence rates in later adolescence. The contribution of genetic and environmental factors to individual differences in sleep duration was dependent on age. Variation in sleep duration at the age of 12 years was accounted for by genetic (boys: 34%, girls: 36%), shared environmental (boys: 28%, girls: 45%), and non-shared environmental factors (boys: 38%, girls: 19%). At the age of 20 years, the role of genetic (boys: 47%, girls: 33%) and non-shared environmental factors (boys: 53%, girls: 67%) was more pronounced. It can be concluded from the results that individual differences in sleep duration were accounted for by genetic and non-shared environmental factors throughout adolescence, whereas shared environmental factors account for a substantial part of variation during early adolescence only.